Development of the composition and modeling of the properties of the biopolymer system for gel cosmetic products with long-lasting actio - Putyatin, Bogdan; Bliznjuk, Olga; Panasenko, Volodymyr; Belinska, Anna; Svishchova, Yana; Zolotukhina, Olena; Ashtaeva, Natalia; Masalitina, Nataliia; Zabrodina, Inna; Kovalova, Tetiana (Technology center PC, 2025)
The object of the study is the properties of a biopolymer system for prolonged delivery of cosmeceutical active ingredients based on natural polysaccharides (sodium hyaluronate and chitosan). The work solves the problem of the lack of a methodology for predicting the properties of a biopolymer system at the design stage. This methodology should link its component composition with functional and structural-mechanical characteristics. The optimization criterion should be achieving a controlled release profile of the hydrophilic active (dexpanthenol) without an initial "explosive" effect. It was established that the optimal ratio is 2.5% sodium hyaluronate and 1.2% chitosan, which ensures the release of 30–35% of dexpanthenol in 6 hours and 60–65% – in 24 hours. Structural and mechanical analysis confirmed the formation of a stable gel with a viscosity of 9800 ± 250 mPa·s and a storage modulus of 325 Pa. This is explained by the formation of a dense polyelectrolyte network due to electrostatic interactions between the anionic groups of sodium hyaluronate. The results of the study of the biopolymer system include the development of approximation models. These models predict the release profile of dexpanthenol based on the concentration of polymers and evaluate the structural and mechanical properties of the biopolymer system. The results obtained can be used in the cosmeceutical industry to create gel products with prolonged action. The effectiveness of the system was confirmed in vitro in phosphate buffer solution (pH 7.4; 37°C). The criterion for effectiveness was the achievement of a controlled release profile: 30–35% of the active substance in 6 hours and 60–65% in 24 hours, which provides a long-term effect without an initial “explosive” effect.
Keywords: biopolymer system; prolonged delivery; release kinetics; structural and mechanical properties; polyelectrolyte complex